Mosaicism for the fragile X syndrome full mutation and deletions within the CGG repeat of the FMR1 gene. Issue 4 (April 1996) - Milà, M; Castellví-Bel, S; Sánchez, A; Lázaro, C; Villa, M; Estivill, X
Abstract : The main mutation responsible for the fragile X syndrome is the expansion of an untranslated CGG repeat in the first exon of the FMR1 gene, associated with the hypermethylation of the proximal CpG island and the CGG repeat region, and repression of transcription of FMR1. Fragile X syndrome mosaicism has been described as the coexistence of the full mutation and the permutation. We present here two cases of mosaicism for the full mutation in the FMR1 gene and deletions involving the CGG repeat region. In one case the deletion removed 113 bp proximal to the CGG repeat and part of the repeat itself, leaving 30 pure repeats, and representing 17% of lymphocytes of the patient. The 5' breakpoint of this deletion falls outside the putative hotspot for deletions in the CGG region of FMR1. In the second case the deleted region only involved the CGG sequence (leaving 15 pure repeats), with normal sequences flanking the repeat; this deleted ("normal") FMR1 was estimated to be in about 31% of blood lymphocytes. This second case can be considered a true regression of the CGG FMR1 expansion to a normal sized allele, although in mosaic form.